Safety Information under Neoliberalism: The Chilean Case - Finkelstein, Rodrigo (Stream: Interdisciplinary Journal of Communication, 2016)
This paper explores the production and supply of safety information under a neoliberal regime, where economic incentives and competition rather than regulations, supervision and enforcement, comprise the common sense to guarantee a safe workplace. Following a political economy of communication framework on the Chilean sector, this assessment unpacks the relationship between Workers’ Compensation Boards’ (WCBs) informational resources and their economic process of exchange within a neoliberal context. The purpose of this paper is to provide a well-grounded theoretical outline to analyse safety information, and to offer a glimpse of the particular kind of informational resources and goods produced by neoliberal WCBs. The following analysis discloses that WCBs are compelled to cede control over their symbolic content to the dynamics of the market place and the logic of profit maximization. Economic and competition imperatives trigger the production, on the one hand, of informational resources as distorted rates, and on the other, of informational goods as pro-corporate safety knowledge. Workers are cognitively misled and left physically and mentally unprotected at the worksite. This paper claims that due to a free market model, Chilean WCBs fail to protect workers’ health and safety by producing and supplying distorted rates and corporate friendly knowledge.